2018
DOI: 10.11594/jtls.08.01.09
|View full text |Cite
|
Sign up to set email alerts
|

Ethnobotany of MandailingTribe in Batang Gadis National Park

Abstract: Batang Gadis National Park (BGNP) located in Bukit Barisan Mountains, Sumatera Utara. A Mandailing tribe who lives around the BGNP, has the unique local knowledge, such as processing young stem of rattan (Calamus manan) into pakkat (traditional food) and use rimbang (Solanum torvum) to neutralize toxins. These local knowledge could be lost because it only inherited orally from generation to generation. This study was aimed to reveal ethnobotany knowledge of Mandailing Tribe. The study was conducted in November… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 7 publications
0
8
0
1
Order By: Relevance
“…The total number of 106 WFPs (85 species) documented represents a relatively high diversity. A recent study in a Mandailing community in North Sumatra showed that 106 food plant species are being used, including wild and cultivated ones [57]. Further in North Sumatra, Batak Toba people from Peadungdung village were found to use 44 species [58].…”
Section: Comparison Of Wild Food Plants Diversity With Other Regionsmentioning
confidence: 99%
“…The total number of 106 WFPs (85 species) documented represents a relatively high diversity. A recent study in a Mandailing community in North Sumatra showed that 106 food plant species are being used, including wild and cultivated ones [57]. Further in North Sumatra, Batak Toba people from Peadungdung village were found to use 44 species [58].…”
Section: Comparison Of Wild Food Plants Diversity With Other Regionsmentioning
confidence: 99%
“…The Solanaceae family with six species of medicinal plants can cure diseases, namely: Physalisangulata / Ciplukan / Kecinoak (treat diabetes and itching of the skin) Solanumlycopercium/ Tomato (treat acne), Solanum melongena / Eggplant / Telung (Treat itching and treat itching boils) Capsicum frutescens / Cayenne Pepper / Chilimbun (treat dog bites and mild venomous animals). In the Mandailing ethnic of the Solanaceae family, the species Inggir-Inggir / turkey berry leaves (Solanumtorvum) is used for eye medications, poisoning and insect venom [32]. A previous study reported that extract of Inggir-Inggir leaves could inhibit the growth of Staphylococcus aureus [33].…”
Section: Diversity Of Rejang Ethnic Medicinal Plantsmentioning
confidence: 99%
“…From the 101 medicinal plant species belonging to 50 families found to be medicinal, it is known that almost all of the organs of the plant are used, starting from roots, rhizomes, stems, leaves, flowers, fruits, seeds, gums. Leaf organs have the most widely used organs, (56 plant species) as well as those found in other regions such as the Mandailing ethnic group [32], the reason leaves are widely used because they are easy to process and have many chemical compounds [37]. For some medicinal plant species, the entire plant organs are used, for example, the species Amaranthusspinosus / spinach thorn, Celosia argentae / arum milek, Celosia cristata.…”
Section: Habitus Plant Organs and Conservation Of Medicinal Plants Umentioning
confidence: 99%
“…Bagian tumbuhan yang paling banyak digunakan oleh Suku Lampung di Kabupaten Lampung Barat dalam pengobatan adalah daun dengan persentase sebesar 43,55% (27 spesies) (Gambar 2). Daun juga merupakan bagian tumbuhan obat yang paling banyak digunakan oleh Suku Mandailing di Taman Nasional Batang Gadis, Sumatera Utara (Nasution et al, 2018), komunitas Dayak Desa di Sintang, Kalimantan Barat (Supiandi et al, 2019), dan Etnis Lokal di Lampung Timur (Evizal et al, 2013). Daun merupakan bagian tumbuhan yang paling mudah didapat, mudah diproses, memiliki efek penyembuhan, dan penggunaannya tidak merusak bagian tanaman (Setyowati, 2010).…”
Section: Hasilunclassified